Spatiotemporal Trends in Temperature and Rainfall in Northwestern Vietnam (2009-2024): 10.32526/ennrj/24/20250046 - Do, Xuan Duc (Environment and Natural Resources Journal, 2025)
The present study sought to optimize the data from eleven Regional Hydro- Meteorological Station in the Northwestern Vietnam. The study results indicated that that the average temperature has tended to increase, which is lower than the average global surface temperature. Still, the maximum temperature, and lowest temperature are higher than the global average (values 0.6, 0.3, and 3.0°C, respectively). The rainy season (23.7°C) generally exhibits warmer temperatures than the dry season (16.9°C). There is a positive correlation between temperatures in consecutive months during both the dry and rainy seasons (r values): 0.75 (September, October), 0.53 (October, December), 0.51 (May, June) 0.46 (August, October), 0.45 (November, December), and 0.38 (April, May), respectively. There is negative correlation between the temperatures of months that are in the same season but far apart, R-values -0.61 (February, December), -0.58 (February, November), -0.56 (April, September), -0.31 (April, October), respectively. The total rainfall and total minimum rainfall showed decreasing trend were 127 mm, and 2.8 mm, respectively. By contrast, total rainfall max tends to increase by 230 mm. The highest rainfall was concentrated from May to October (1,219 mm). Higher correlation values for rainfall were observed in winter (January to March, and October to December), at 0.65, 0.78, 0.85, 0.93, 0.94, and 0.99 compared to summer (April to September), with r values of 0.29, 0.36, 0.57, 0.42, and 0.45, respectively. In a year, positive correlations between temperature and rainfall predominate most months of spring (January, February, and March), autumn (July, August, and September), and winter (October, November, and December), R-values: 0.59, 0.36, 0.44, 0.53, respectively, while negative correlations are more common in April, May, and June (summer) with the r values of -0.33, -0.16, and -0.25, respectively. The present study may provide a valuable and future climate, and rainfall projections.